Association between nickel exposure and diabetes risk: an updated meta-analysis of observational studies - Lu, Huaye; Shi, Xiaoyang; Han, Lei; Liu, Xin; Jiang, Qingtao (Frontiers in Public Health, 2024)
Objective The results of epidemiological studies on the association between nickel exposure and diabetes remain controversial. Therefore, an update meta-analysis was conducted to examine the association between urinary nickel levels and diabetes risk, and to focus on whether there is an association between blood nickel levels and diabetes risk. Methods Relevant studies were comprehensively searched from PubMed, Web of Science, and Wanfang databases from their inception to July 2024. The random-effects model was utilized to determine pooled Standard Mean Difference (SMD) and 95% confidence intervals (CIs), with stratified and sensitivity analyses also performed. Heterogeneity between studies was assessed using I2 statistic, while publication bias was evaluated using Egger's and Begg's tests. The quality of the included studies was assessed using the Newcastle-Ottawa Scale. Results A total of 19 studies involving 46,071 participants were included in this meta-analysis. The random-effects model indicated that the pooled SMD for nickel exposure levels in diabetic patients and non-diabetic controls were 0.16 (95% CI 0.07–0.2) for urine and 0.03 (95% CI −0.20 to 0.27) for blood, respectively. Conclusion It was discovered that diabetes risk was positively correlated with urinary nickel levels, whereas there was no significant correlation with blood nickel levels. Furthermore, it appeared that the association between nickel exposure and diabetes risk differ in individuals with diabetes compared to those with pre-diabetes, and that the direction of the correlation may even be reversed. In conclusion, more high-quality prospective studies are needed in order to validate these findings in future research endeavors. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO, registration number: CRD42024534139.